Influence of dietary sesame meal, vitamin E and selenium supplementation on milk production, composition, and fatty acid profile in dairy goats - Mitsiopoulou, Christina; Karaiskou, Christina; Simoni, Marica; Righi, Federico; Pappas, Athanasios C.; Sotirakoglou, Kyriaki; Tsiplakou, Eleni (My University, 2021)
Although sesame oil meal is rich in linoleic acid, and both selenium (Se) and vitamin E (VitE) protect prone-unsaturated fatty acids (UFA) from oxidation, their influence on goats’ milk fatty acids (FAs) profile have not been studied. Thus, thirty dairy goats were divided into five groups and fed with alfalfa hay and concentrates. Two types of concentrates were used; one for the control (CON) and another for the treated groups. In the concentrate of the treated groups which contained sesame oil meal, apart from the quantities of VitE and Se included in the trace mineral-vitamin premix, either no extra VitE and Se (SOM) or extra 60 mg of VitE/Kg of concentrate (SOME), or 0.1 mg organic Se/Kg of concentrate (SOMSe) or its combination (60 mg of VitE and 0.1 mg organic Se/Kg of concentrate) (SOMESe) were incorporated. In blood plasma, the proportion of C14:0 reduced significantly in the SOME-fed goats compared with CON-fed goats while that of C16:0 reduced significantly in those goats fed the SOM, SOMSe, SOMESe diets. The proportions of medium-chain FAs (MCFA) and saturated FAs (SFA), and the atherogenicity index value reduced significantly in the milk of treated animals. Significant was also the decline in the SFA/UFA ratio in the milk of goats fed with the SOM, SOME and SOMESe diets. On the contrary, the proportions of long-chain FAs in the milk of SOM and SOMESe fed goats increased significantly. A significant increase in the proportions of UFA in the milk of SOME and SOMESe-fed goats and in the proportions of MUFA in those goats fed the SOM, SOME and SOMESe diets was found. In conclusion, the SOMESe diet can be considered as the most effective nutritional strategy to affect positively the goats’ milk FAs profile since the sharpest modifications in the aforementioned FAs were observed with this dietary treatment.
Keywords: Sesame; Vitamin E; Fatty acid; Goats; Milk; Plasma